Treatment and outcome of metastatic parathyroid carcinoma: A systematic review and pooled analysis of published cases - Alberti, Andrea; Smussi, Davide; Zamparini, Manuel; Turla, Antonella; Laini, Lara; Marchiselli, Chiara; Grisanti, Salvatore; Bossi, Paolo; Berruti, Alfredo (Frontiers in Oncology, 2022)
Background Parathyroid carcinoma (PC) is an extremely rare malignant tumor with an incidence of about 6 new cases per 10 million inhabitants per year. While several papers have been published on treatments and outcomes of PC patients with loco-regional disease, little is known about the prognosis, treatment strategies, and prognostic factors of patients with distant metastasis. Materials and methods We performed a systematic review and a pooled analysis of histopathologically confirmed PC cases published in literature using the following keywords: “metastasis–metastatic–secondary nodes” AND “parathyroid carcinoma”. Original case reports and case series reporting metastatic parathyroid carcinoma were included. Data from 58 articles were extracted in a piloted form by five reviewers on a shared database. Results Seventy-nine patients with metastatic PC were identified between 1898 and 2018. Ten (13%) patients had synchronous metastases, while metachronous metastases occurred in 43 (54%) patients. The remaining 26 patients developed metastatic disease concomitantly to local recurrence. Primary hyperparathyroidism guided the diagnosis of metastatic recurrence in 58 (73%) patients. Surgery was the main primary approach adopted, as it was performed in 43 (54%) patients. Twenty (25%) patients underwent systemic antineoplastic therapy, consisting of chemotherapy, immunotherapy, tyrosine kinase inhibitors, and hexestrol therapy. Bone resorption inhibitors had a limited efficacy in the long-term control of hypercalcemia. After a median follow-up of 37.5 months, 43 (55%) patients died, 22 (51%) due to the consequences of uncontrolled PHPT. The median overall survival was 36 months (range: 1–252). Surgery was associated with a better OS (HR 0.48, 95% CI 0.26–0.88), whereas bone metastases represented a negative prognostic factor (HR 2.7, 95% CI 1.4–5.2). Conclusion Metastatic PC has a relatively poor prognosis. The main goals of treatment are to counteract tumor growth and control hypercalcemia. Surgery of metastases is the best approach to achieve rapid control of PHPT and longer survival. Target therapies and immunotherapy deserve to be extensively tested in metastatic PC and strategies to better control hypercalcemia should be implemented.